Drug-Drug Interaction Study of Ketoconazole and Ritonavir-Boosted Saquinavir - Kaeser, Benoite (American Society for Microbiology (ASM), 2009)
Saquinavir, a potent human immunodeficiency virus protease inhibitor, is extensively metabolized by CYP3A4. Saquinavir is coadministered with ritonavir, a strong CYP3A4 inhibitor, to boost its exposure. Ketoconazole is a potent CYP3A inhibitor. The objectives of this study were to investigate the effect of ketoconazole on the pharmacokinetics of saquinavir/ritonavir and vice versa using the approved dosage regimens of saquinavir/ritonavir at 1,000/100 mg twice daily and ketoconazole at 200 mg once daily. This was an open-label, randomized two-arm, one-sequence, two-period crossover study in healthy subjects. In study arm 1, 20 subjects received saquinavir/ritonavir treatment alone for 14 days, followed in combination with ketoconazole treatment for 14 days. In arm 2, 12 subjects received ketoconazole treatment for 6 days, followed in combination with saquinavir/ritonavir treatment for 14 days. The pharmacokinetics were assessed on the last day of each treatment (days 14 and 28 in arm 1 and days 6 and 20 in arm 2). The exposures C(max) and the area under the concentration-time curve from 0 to 12 h (AUC(0-12)) of saquinavir and ritonavir with or without ketoconazole were not substantially altered after 2 weeks of concomitant dosing with ketoconazole. The C(max) and AUC(0-12) of ketoconazole, dosed at 200 mg once daily, were increased by 45% (90% confidence interval = 32 to 59%) and 168% (90% confidence interval = 146 to 193%), respectively, after 2 weeks of concomitant dosing with ritonavir-boosted saquinavir (1,000 mg of saquinavir/100 mg of ritonavir given twice daily). The greater exposure to ketoconazole when given in combination with saquinavir/ritonavir was not associated with unacceptable safety or tolerability. No dose adjustment for saquinavir/ritonavir (1,000/100 mg twice daily) is required when coadministered with 200 mg of ketoconazole once daily, and high doses of ketoconazole (>200 mg/day) are not recommended.